Complexed zinc and manganese supplementation on live and processing performance in broiler chickens - Sanfelice, C. [UNESP]; Bilgili, S. F.; Hess, J. B.; Mendes, A. A. [UNESP] (My University, 2015)
In this study, the influence of dietary complexed zinc (CZn) and manganese (CMn) supplementation on growth performance (BW, feed conversion and mortality), incidence of foot pad dermatitis (FPD), litter quality, skin quality (bruises, broken wing and leg, cuts and scratches) and processing yield of broilers was assessed at 49 d of age. A total of 1,120 male broilers were assigned to 4 dietary treatments: (1) Inorganic control diet (IC) which provided 80 ppm ZnSO4 and 90 ppm MnSO4; (2) Same as IC, except CZn replaced 40 ppm of Zn from ZnSO4 (IC+CZn-Zn); (3) IC plus additional 40 ppm of CZn (IC+CZn); (4) Same as IC, except CZn and CMn replaced 40 ppm of Zn and Mn (IC+CZn+CMn). Each treatment was provided in a 3-stage feeding program. Broilers reared on IC+CZn and IC+CZn+CMn showed improvement (p≤0.05) in BW at 28 and 49 d of age when compared to inorganic control diet (IC). No differences in carcass, FPD and component yields were detected because of dietary treatments. In this study, complexed zinc and manganese supplementation only had a significant improvement on broiler BW and feed conversion.
Keywords: Broiler; Foot pad dermatitis; Mineral; Skin quality